ФІНАНСОВЕ ЗАБЕЗПЕЧЕННЯ ФУНКЦІЙ В СИСТЕМІ ОРГАНІВ МІСЦЕВОГО САМОВРЯДУВАННЯ В УКРАЇНІ (Світ фінансів, 2017)
Серебрянська Д. М. Фінансове забезпечення функцій в системі органів місцевого самоврядування в Україні. Проаналізовано стан дохідної спроможності кожного із виду місцевих бюджетів окремо за період дії Бюджетного кодексу України 2002–2010 рр. та 2011–2013 рр. Виявлено, що прийняття нових положень Бюджетного кодексу України не вплинуло на підвищення доходів місцевих бюджетів, формування яких зводиться до забезпечення певного мінімуму бюджетних коштів. Акцентовано, що базова ланка місцевого самоврядування поступово втрачає своє функціональне призначення через дефіцит фінансових ресурсів. Обґрунтовано пропозиції щодо проведення ефективної бюджетної децентралізації в Україні. Серебрянская Д. М. Финансовое обеспечение функций в системе органов местного самоуправления в Украине. Проанализировано состояние доходной способности каждого вида местных бюджетов за период действия Бюджетного кодекса Украины 2002–2010 гг. и 2011–2013 гг. Определено, что принятие новых положений Бюджетного кодекса Украины не повлияло на повышение доходов местных бюджетов, формирование которых сводится к обеспечению определенного минимума бюджетных средств. Акцентировано, что базовое звено местного самоуправления постепенно теряет свое функциональное назначение из-за дефицита финансовых ресурсов. Обоснованы предложения по проведению эффективной бюджетной децентрализации в Украине. Serebrianska D. Financial support for the functions in the system of local governments in Ukraine. Efficiency of the fiscal decentralization in Ukraine depends on economically justifi ed division of responsibilities between local governments and local budgets revenue. In the context of the last factor the revenue capacity of each type of local budgets is separately analyzed in the article for the Budget Code of Ukraine as revised in 2002-2010 and for the Budget Code of Ukraine as revised in 2011-2013. After the detailed analysis, it was found that the adoption of the new provisions of the Budget Code of Ukraine did not affect budgets revenue, because during budgets calculations revenue was reduced to cover only basic costs. It was founded that the main factors that caused stated problem are improper legislative regulation and effortless behavior of the local authorities due to the lack of responsibilities for a specific function. It was established that the basic element of local self-government is gradually losing its functionality due to lack of financial resources. As a result, the main authority that provides local public goods and services to rural communities are local governments of district level, which contradicts to the idea of fiscal and administrative decentralization. It were justified an initiatives for effective fiscal decentralization in Ukraine.